Continuous testing of silica-PEI adsorbents in a lab.-scale twin bubbling fluidized-bed system. (March 2019) - Kim, Jae-Young; Woo, Je-Min; Jo, Sung-Ho; Lee, Seung-Yong; Moon, Jong-Ho; Kim, Hyunuk; Yi, Chang-Keun; Lee, Hyojin; Snape, Colin E.; Stevens, Lee; Sun, Chenggong; Liu, Hao; et al.
Highlights: A lab.-scale twin bubbling fluidized-bed CO2 capture system has been developed. Two kinds of silica-PEI adsorbents have been evaluated in a continuous way. The CO2 removal efficiency of above 80% was achieved. The dynamic sorption capacity of above 6.0 wt.% was achieved. Abstract: In this study, a lab.-scale twin bubbling fluidized-bed system (TBS) has been used continuously to test the performance for CO2 adsorption of silica-PEI (S.PEI) adsorbents, containing 40 wt.% of PEI, which were supplied by the University of Nottingham (UNOTT). The TBS comprises bubbling-bed adsorption and desorption reactors, a riser for pneumatic conveying of solids from the adsorption to the desorption reactor, and a cyclone for solid-gas separation. The adsorbent prepared using PEI with a molecular mass of 800 (S.PEI-0.8K) was a preliminarily tested for almost 24 h at the given operating conditions by varying the inlet sorbent/CO2 mass ratio at the adsorber to analyse the CO2 removal efficiency in the adsorption reactor and the dynamic sorption capacity of the adsorbent. A 180-h continuous test was then carried out by changing various experimental conditions such as the H2 O concentration, reaction temperature, solid layer height, reaction gas flow rate, and inlet sorbent/CO2 mass ratio at the adsorber using PEI with a molecular mass of 5000 (S.PEI-5K) adsorbent. In this test, a CO2 removal efficiency of above 80% and a dynamic sorption capacity greater than 6.0 wt.% were achieved.